PROGRAM PELATIHAN INVESTIGASI PENYAKIT HEWAN MENULAR BAGI MAHASISWA PENDIDIKAN PROFESI DOKTER HEWAN DI KUPANG - Gelolodo, Maria Aega; Simarmata, Yohanes Timbun Raja Mangiut Ronael; Kallau, Novalino Harold Geoffrey; Tabali, Zulkifli; Sitompul, Yeremia Yobelanno; Loe, Fhady Risckhy; Wuhan, Yustinus Oswin Primajuni (Jurnal Media Tropika, 2025)
Infectious animal diseases, particularly zoonoses, pose a significant problem to the inhabitants of East Nusa Tenggara (NTT) Province because of the high animal population, especially livestock, and the close interaction between humans, animals, and the environment. The Faculty of Medicine and Veterinary Medicine, Universitas Nusa Cendana, Kupang, held the Animal Disease Investigation Training Program for Veterinary Professional Education Students (PPDH) to overcome this significant challenge. This one-day workshop had been attended by 80 participants, consisting of 26 men (32.5%) and 54 women (67.5%). This training aims to improve students' understanding and skills in zoonotic disease investigation through theoretical and practical approaches. Theoretical sessions were conducted by giving presentations to provide a foundation of knowledge. At the same time, interactive approaches in the form of group discussions and field practice were designed to improve the ability to analyze and handle cases in the field. The results of this training are expected to equip participants with the ability to investigate, identify risks, and implement disease prevention and control measures. The expected implication of this activity is to improve the ability of prospective veterinarians to face the challenges of animal diseases in NTT, especially in infectious disease detection. This training provides relevant theoretical and practical experience in protecting animal and public health in the region.